Causing trouble and being transmissible: COVID-19 survivors’ experiences of stigma and discrimination in South Korea - Kang, Jiyeon; Kim, Hyang Soo; Yi, Hyun Ji; Lee, Yesung; Lee, So Hee; Song, Kyoung-Ho; Park, Hye Yeon; Oh, Hong Sang; Yoon, Doran; Choe, Pyoeng Gyun; Lee, Eun Joo; Choi, Chi-Hyun; et al. (Frontiers in Psychiatry, 2023)
Background The stigma associated with coronavirus disease (COVID-19) is relatively neglected in policies for handling the disease. Stigmatization occurs only within specific social contexts in local societies. Objective This study aims to examine COVID-19 survivors’ experiences of social stigma and discrimination in South Korea in the first 2 years of the pandemic. Methods Semi-structured interviews were conducted. Results Of 52 participants, 45 reported that they had to cope with stigma and discrimination in their intimate social relationships, workplaces, and children’s schools, ranging from subtle actions to job loss. Sexual minorities who were involved in mass disease transmission in the early part of the pandemic experienced a higher level of stigmatization. The stigmatization dealt with in this study was related to two themes: survivors’ sense of causing trouble and possibility of transmission. Conclusion By intertwining this stigma with the experiences of public health measures through the voices of survivors, this study reveals the local context of East Asia in terms of culture-specific aspects of COVID-19-related stigma.